Reciprocal Technique to Improve the Novice Learners’ Speaking Proficiency - Utama, Yoga Alif Kurnia; Kurniawan, Yohanes (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2018)
Speaking proficiency becomes a priority in leaning foreign language. However, preliminary observation done showed that speaking skill was not the objective in most English classes. It was also found that the students were passive. By applying Research and Development design of Pimsleur‟s reciprocal technique, this study aims to improve the novice learners‟ speaking proficiency. After applying design of Pimsleur‟s reciprocal technique, there are some results. Based on the analysis, it can be concluded that the Indonesian adaptation of Pimsleur‟s method is an appropriate media to teach transactional conversation to low level students. The results show that the simple real situations based audio content is suitable and useful to the students‟ need. The principles used also ease the students to acquire, store, recall, practice, and communicate in English, as the target language, correctly. And the participants give positive responses to the use of the Indonesian adaptation of Pimsleur‟s method